The Fair Value – Representation of the Market Value in Accounting. Trends and Perspectives in Romanian Accounting Practice - Marinela-Daniela Manea (CES Working Papers, 2011)
The market value, as a method of measuring the right value, also provides the highest objectivity due to the fact that it is based on information exterior to the entity, impossible to influence in any way. For the fair value of a product to be equivalent to the market value, a prerequisite needs to be followed: the market must be perfect, namely organized and active. In this case, the evaluation's type is market to market. In certain fields, the active's market existence is clearly difficult (for instance for the derived products or specialized, unique assets etc). In such situations – imperfect market – we will valorize that specific good by calculating its fair value by using an evaluation technique, an alternative technique in the absence of a price set by the market. There are two possible approaches: the first one belongs to the analogy method; the second approach belongs to valuing an asset using the modeling technique also known as market to model. The method of determining the value of an asset by analogy or similarity is theoretically valid, but in practice this is difficult, since the notion of similar characteristics is often difficult to establish and prove. This article proposes a valuation of the market value concept based on Romanian realities - legal, accounting practices in that area, and taking into account the existing fiscal limitations.
Keywords: 330; market value; fair value; comparison approach; the analogy method; identical or similar assets sales; the modeling technique Romania